Star formation history and dynamical evolution of the solar neighbourhood - Just, Andreas; Sysoliatina, Kseniia (Proceedings of the International Astronomical Union, 2018)
We used our detailed analytic local disc model to compare predictions in number counts, colour distribuitons and kinematics with a data set extracted from a combination of TGAS and RAVE catalogues. We find generally a very good agreement with some deviations close to the Galactic plane.
Gesehen am 03.09.2019